THE ROLE OF THE “ARMENIAN LIBRARY” PERIODICAL OF THE LIBRARY ASSOCIATION OF ARMENIA (Bulletin of Armenian Libraries, 2023)
In 1941, State Public Library after Al. Myasnikyan (now the National Library of Armenia) published the “Bibliographical Magazine” that was the basis for library and bibliographic periodicals published later, such as “Librarian,” “Culture-Enlightenment Work,” and “Culture.”  After independence of Armenia, the creation of the Library Association of Armenia played a major role in the library sector. From 1996-2008, the Association’s periodical was published, which reflected not only the life of the library association, but also was an important platform for those of the library sector. Leading specialists, scientists, lecturers, cultural figures, and students published and disseminated their articles. The presentation attempts to discuss the role and significance of the only periodical of the Library Association of Armenia, and the analysis and assessment of the articles published in magazines within the context of present day.